2015
DOI: 10.1063/1.4907319
|View full text |Cite
|
Sign up to set email alerts
|

Thickness dependent quantum oscillations of transport properties in topological insulator Bi2Te3 thin films

Abstract: The dependences of the electrical conductivity, the Hall coefficient, and the Seebeck coefficient on the layer thickness d (d ¼ 18À600 nm) of p-type topological insulator Bi 2 Te 3 thin films grown by thermal evaporation in vacuum on glass substrates were obtained at room temperature. In the thickness range of d ¼ 18-100 nm, sustained oscillations with a substantial amplitude were revealed. The observed oscillations are well approximated by a harmonic function with a period Dd ¼ (9.5 6 0.5) nm. At d > 100 nm, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…One can see that the increase in RH with temperature is observed for the crystal only, which can indicate that since the diffusion rate in thin films is higher, the probability of the occurrence of nonequilibrium states decreases. Another reason could be that in contrast to a polycrystal, a film has a certain orientation [18]. However, as an increase in RH with temperature is observed in single crystals too [3,14,15], apparently, orientation does not account for the increase in RH under increasing temperature.…”
Section: Polycrystals With P-type Conductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…One can see that the increase in RH with temperature is observed for the crystal only, which can indicate that since the diffusion rate in thin films is higher, the probability of the occurrence of nonequilibrium states decreases. Another reason could be that in contrast to a polycrystal, a film has a certain orientation [18]. However, as an increase in RH with temperature is observed in single crystals too [3,14,15], apparently, orientation does not account for the increase in RH under increasing temperature.…”
Section: Polycrystals With P-type Conductivitymentioning
confidence: 99%
“…% Te, S, RH and H practically do not change with the composition. It was shown that the composition of crystals with different stoichiometry and type of conductivity is fairly well reproduced in films obtained by thermal evaporation in vacuum of these crystals [16][17][18].…”
Section: Introductionmentioning
confidence: 97%
“…The well-known examples are the quantum oscillations in resistivity (Shubnikov-de Haas effect) and in magnetization (de Haas-van Alphen effect) caused by Landau quantization due to the magnetic field [5]. Energy level quantization due to size effects also causes quantum oscillations in certain thermodynamic and transport properties [6][7][8][9][10][11][12][13][14][15] of various semiconductor and metallic nanostructures which have been extensively studied due to their importance on nanoscale electronics and nano-engineered devices [16][17][18][19]. In low dimensional materials, quantum size effects [3,20,21] become stronger and give rise to distinct subbands [22] and size quantization effect [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…specific heat [25][26][27][28][29], thermopower [30,31]) appear due to the nature of Fermi-Dirac distribution function and its derivative with respect to energy (so called occupancy variance or thermal broadening function) respectively [32][33][34]. Size-dependent quantum oscillations attracted a great deal of interest particularly in recent decades [6,[8][9][10][11][12][13][14][15]35].…”
Section: Introductionmentioning
confidence: 99%
“…Thermodynamic properties like entropy and specific heat capacity at constant volume, thermoelectric properties such as Seebeck coefficient and electronic transport properties such as charge carrier mobility, electrical and thermal conductivities are some examples of these oscillatory quantities [4,. Examination of size dependent oscillations also has crucial importance in superconductors and topological insulators [33,34,[36][37][38][39]. Size and density dependent oscillations in aforementioned quantities are attributed to the quantization of energy spectrum and fluctuations in density of states around Fermi level at nanoscale [15][16][17][18][19][20]40].…”
Section: Introductionmentioning
confidence: 99%